La forêt mixte du Québec dans la perspective historique - Rousseau, Jacques (Cahiers de géographie du Québec, 1962)
The mixed forest of the St. Lawrence valley, which presents jour successive landscapes during its seasonal rhythm, bas been the dorsal spine of Eastern Canada s economy since the establishment of the French colony.The various people who have successively inhabited this forest have either used it as members of the bio-sociological unit or tried to modify its ecology, depending on their traditional culture. It was occupied soon after the glacier recession by the Red-ochre Man, who was followed by the Algonkian forest hunters. Later, the same territory was inhabited by Iroquoian tribes, who brought with them their agriculture which had evolved in the South, but was reoccupied by the Algonkian tribes just before the foundation of Québec. At this time it became a country of European settlers, who carried with them their Old World agriculture and tried to reconstruct in a new continent their Normandie or Poitou landscape. For a newly established agriculturist, the land hardly produced enough for a living. The exploitation of Canadian forests was unpopular amongst the LaRochelle merchants who preferred to trade in the Baltic regions. The first important economic resource was the fur trade. Later, when Napoleon Bonaparte set up a blockade in the Baltic sea, England had to look elsewhere to save and develop her navy and found in the forests of Eastern Canada the pine-trees she needed. Finally, the increase in the number of news-papers, which was largely a consequence of the French revolution, developed another type of forest industry, the production of spruce pulp.